Association between KIR gene polymorphisms and type 1 diabetes mellitus (T1DM) susceptibility: A PRISMA-compliant meta-analysis. Issue 52 (December 2017) - Liu, Shu-Lan; Zheng, A-Juan; Ding, Li
Abstract: Background: Type 1 diabetes mellitus (T1DM) is a T-cell mediated autoimmune disease with a complex genetic and immunological background. Evidence suggests that killer cell immunoglobulin-like receptor ( KIR ) genes are associated with T1DM, but the results are inconsistent. Here, we conducted a meta-analysis to comprehensively evaluate the effect of KIR genes on the risk of T1DM. Methods: The PubMed, Web of Science, the Chinese Biomedical Database, and Chinese National Knowledge Infrastructure databases were systematically searched to select studies on the association between KIR polymorphisms and T1DM. The quality of each study was scoring in term of the Newcastle–Ottawa Scale. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of this association. Subgroup analysis stratified by ethnicity was also conducted. Funnel plot and Egger test were conducted to assess the publication bias. Results: A total of 13 independent case–control studies comprising 2076 T1DM cases and 1967 controls were included in this meta-analysis. We found a negative association between the KIR2DL1 polymorphism and susceptibility to T1DM in the overall population (OR = 0.71, 95%CI = 0.51–0.98, P  = .038), but not in ethnic-specific analysis. Additionally, a negative association between the KIR2DS1 polymorphism and susceptibility to T1DM was found in the Asians (OR = 0.76, 95%CI = 0.63–0.92, P  = .004), but not in the Caucasians. However, the associations could not withstand Bonferroni correction. Conversely, no association between the other KIRs genes ( KIR2DL2, KIR2DL3, KIR2DL4, KIR2DL5, KIR2DS2, KIR2DS3, KIR2DS4, KIR2DS5, KIR3DL1, KIR3DL2, KIR3DL3, and KIR3DS1 ) and T1DM susceptibility was found in overall and subgroup ethnicity. No publication bias was detected in all comparisons. Conclusions: In summary, this meta-analysis suggested that the KIR2DL1 and 2DS1 polymorphism might be a potential protective factor for T1DM in the specific ethnicity. Further subtle design studies with more sample size are still needed for a definitive conclusion.